Motivational profile of participants in a home physical activity program during the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: For the promotion of physical activities with adherence adjustments, if necessary, understanding all levels of factors that can influence participation. Objective: To identify the motivational profile of participants in a physical activity program and the reasons for which participants seek the project. Methodology: This is a descriptive study based on the remote physical activity program proposed during the pandemic by “Musculação UESC” extension project. A total of 125 applicants were contacted to conduct an interview via call for a pre-assessment of participation. In this pre-assessment, the instruments an, PAR-Q, online motivational profiles (IMPRAF-54 and BREQ-3) were used, all adapted in form. Of these, 39 agreed to participate in the interviews carried out by one of the members of the Extension Project team. Results: the participants showed a motivational profile with the highest intrinsic motivation and the most self-determined types of behavioral regulations identified. The main reasons reported by the participants were related to pleasure and health considered as more intrinsic reasons. A trend was observed among men who were identified as having the highest Indicator Scores, presented and in which the greatest reasons for competition and pleasure. The reasons were correlated with the identified solutions, regulation and intrinsic regulation, of more self-determined regulations. And it was age correlated with the identified. Conclusion: The participants in a program of remote physical activities during a pandemic have more self-determined behavioral regulations and intrinsic motives. Keywords: COVID 19 pandemic; Physical exercise; Motivation.